2022
DOI: 10.1186/s12888-022-03748-y
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on sleep disturbances and associated factors among nurses

Abstract: Background Many studies have measured sleep disturbances among nurses globally, but none have addressed this issue in Vietnam. Therefore, this study aimed to assess the prevalence of sleep disturbance and identify associated factors among staff nurses in Vietnam. To identify sleep disturbances and associated factors among staff nurses in Vietnam. Methods A cross-sectional design was used in this study. Participant nurses (n = 420) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Our study findings are also consistence with some international studies. 9 - 10 The variations in the prevalence of sleep disorders might be because of different tools used in classifying sleep disorders. Studies have shown health care professionals are more vulnerable to poor sleep than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings are also consistence with some international studies. 9 - 10 The variations in the prevalence of sleep disorders might be because of different tools used in classifying sleep disorders. Studies have shown health care professionals are more vulnerable to poor sleep than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size for this study was estimated using the following formula: n = Zα/2^2 x P (1-P)/d^2. Based on a previous studies [45][46][47][48][49], the prevalence of sleep disorders in patients with orthopedic trauma was estimated to be 40%. With a margin of error of 5%, a confidence level of 95%, and a non-response rate of 10%, the estimated sample size was 265.…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, fewer studies on quality of life were conducted among healthcare workers than other groups such as patients or the general population although studies on job satisfaction, [ 21 ] stress, [ 22 ] burnout, [ 23 ] quality of sleep [ 24 ] or anxiety and depression [ 25 ] were conducted. With a much smaller healthcare worker density than the world average (60 vs. 174/10,000 people), [ 26 ] there was a significant increase in the number of healthcare workers experiencing both mental and physical health problems, especially during the COVID-19 outbreak [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%